2020
DOI: 10.1155/2020/3183206
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study on Hysteretic Behavior of Double‐Plate Reinforced Overlapped K‐Joints

Abstract: The lifetime of hollow section tubular joints frequently can be shortened owing to the occurrence of the welded cracks and the plastic deformation of chords under the cyclic loading, because of the deficient radial bearing capacity of the steel tube. To avoid such failures, this paper proposes a novel method to strengthen the chord with double plates at the intersection of the chord and braces. To further investigate the efficiency of this strengthening method on hysteretic performance and energy depletion abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…Lee et al [31] compared the fatigue performances of nonoverlapped and partially overlapped K-joints under different loading conditions and concluded that a partially overlapped K-joint is superior to its nonoverlapped counterpart as most of the members in actual truss design are assumed to be axially loaded only. Other investigations include fatigue behavior of overlapped tubular joints with an overlapping ratio (i.e., the overlapped length to the brace diameter) larger than 50% [6,7,32], hysteretic behavior of reinforced overlapped joints [33], and local joint flexibility and strength of overlapped tubular joints [34][35][36].…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…Lee et al [31] compared the fatigue performances of nonoverlapped and partially overlapped K-joints under different loading conditions and concluded that a partially overlapped K-joint is superior to its nonoverlapped counterpart as most of the members in actual truss design are assumed to be axially loaded only. Other investigations include fatigue behavior of overlapped tubular joints with an overlapping ratio (i.e., the overlapped length to the brace diameter) larger than 50% [6,7,32], hysteretic behavior of reinforced overlapped joints [33], and local joint flexibility and strength of overlapped tubular joints [34][35][36].…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%